Mulheres em segredo e o segredo das mulheres: invisibilidade e resistência em um quilombo contemporâneo da Amazônia - LOPES, Carla Joelma de Oliveira (2019)
The changes in Brazilian legal frameworks, especially the adoption of the 1988 ADCT, encouraged several quilombola communities to seek land regularization, but the process was marked by intense disputes. The struggles and mobilizations for the territorial security of the quilombola people were accompanied by retaliation by the public power and the private capital, since the alien interest in the lands of the Amazon goes back to the end of the decade of 1960 through the entrance of the Great Projects and extends to the present day. In this scenario, the women leaders of the quilombos who have shown their political strength stand out. This is the case of Araquembaua in Baião - PA. The quilombola women in this community have been protagonists of coping movements that have been marking the local trajectory, contradictorily, however, have also been invisibilized. The general objective of the research is to analyze the political agency of these women against the invested of the Great Enterprises on their territory. For this, we look for clues about this reality in the daily life of the place and in the historiographical literature. The results indicate that the women 's participation in the process made the movement for the socio - territorial resistance and resistance of the quilombo of Araquembaua to be differentiated.